High density fiber postitioner system for massive spectroscopic surveys. Issue 3 (10th September 2018) - Hörler, Philipp; Kronig, Luzius; Kneib, Jean-Paul; Bouri, Mohamed; Bleuler, Hannes; von Moos, Dieter
ABSTRACT: We describe here a novel design of a fast high-density robotized fiber positioner system for massive spectroscopic surveys. The fiber positioners are compact, robust, and they can be coordinated, allowing for a high spatial density. Furthermore, the high absolute accuracy removes the need for a metrology system and reduces the reconfiguration time. First, we present the requirements for such a high-density fiber positioner system and put them in relation with the science goals. Then, we discuss the positioner design that accomplishes these requirements (including mechanical design, local control electronics board, overall communication solution, and observation sequencing). Finally, the performance of the proposed design is measured using 25 mm pitch prototypes of the positioners, through a dedicated novel designed test-bench. The related results show that our prototypes fulfil the requirements particularly in terms of positioning precision (<20 µm rms for one single open loop move) and partially in tilt (<0.15 deg).